A comprehensive method of e-government transition for viable development in Iraq - Ahmed Fakhir Mutar; Ahmed Rashid Abdullah; Osamah Mohammed Jasim; Murtaja Ali Saare; Saima Anwar Lashari (Bulletin of Electrical Engineering and Informatics, 2022)
Now more than ever, the government needs to find out that how well the system of Iraq can be transformed to efficiently offer public services to the citizens for consistent development growth. For many reasons, the answer lies in the development, innovation, and application of the latest technologies in Iraq. The use of electronic technology will offer fast and convenient access to public services and will allow the people of Iraq to participate in decision-making and designing and delivery of the services. These technologies assist in government openness, increasing accountability, and boosting public trust. A comprehensive approach that is based on the 4 key pillars to support the e-government transition of Iraq for consistent development growth is presented in this paper. This approach provides guidelines to the government of Iraq that encourage the application of technology for the betterment of people regardless of their age, sex, religious and political beliefs, financial status, disabilities, and area. It highlights the need of e government transition and provides a plan to focus on the key pillars to develop abilities for viable development growth in Iraq.